Woreda Level Participatory Land Use Planning (WLPLUP) Approaches in Pastoral and Agro Pastoral Areas of Ethiopia - Terefe, B.; Asefa, W. (International Livestock Research Institute, 2022)
Woreda Level Participatory Land Use Planning (WLPLUP) Approaches In Pastoral and Agro Pastoral Areas of Ethiopia